The Role of RNA Methyltransferase METTL3 in Normal and Malignant Hematopoiesis - Wu, Xia; Ye, Wu; Gong, Yuping (Frontiers in Oncology, 2022)
m6A modification is the most common modification in eukaryotes. METTL3, as a core methyltransferase of m6A modification, plays a vital role in normal and malignant hematopoiesis. Recent studies have shown that METTL3 is required for normal and symmetric differentiation of hematopoietic stem/progenitor cells (HSPCs). Moreover, METTL3 strongly impacts the process and development of hematological neoplasms, including the differentiation, apoptosis, proliferation, chemoresistance and risk of tumors. Novel inhibitors of METTL3 have been identified and studied in AML cells. STM2457, a selective inhibitor of METTL3, has been identified to block proliferation and promote differentiation and apoptosis of AML cells without impacting normal hematopoiesis. Therefore, in our present review, we focus on the structure of METTL3, the role of METTL3 in both normal and malignant hematopoiesis, and the potential of METTL3 for treating hematological neoplasms.